ANALISIS EFISIENSI DISTRIBUSI DAN TINGKAT KETEPATAN PENDISTRIBUSIAN PROGRAM RASTRA DAN BPNT PADA RUMAH TANGGA PENERIMA MANFAAT DI KELURAHAN YUKUM JAYA, KABUPATEN LAMPUNG TENGAH - Annisa Nevy Prihartini; Raden Hanung Ismono; Zainal Abidin (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to determine the distribution system, efficiency, and accuracy of the distribution of Beras Sejahtera (RASTRA) and Bantuan Pangan Non-Tunai (BPNT) programs in Yukum Jaya Village, Terbanggi Besar Sub-district, Central Lampung Regency.  The attributes used in this study are right on target, right on amount, right on time, right on price, right on administration, right on quality consisting of color, aroma, rice cleanliness, and condition of eggs.  The study uses a survey method involving 33 recipients of Rastra program and 31 recipients of BPNT program.  The first and second objectives are analyzed using qualitative and quantitative descriptive analysis.  The third objective is analyzed using Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA).  The study shows that the distribution system of Rastra and BPNT are included in the semi-direct distribution category.  The distribution efficiency of the Rastra program is 0..06 and the BPNT program is 0.04 which means that the distribution of rice in the two programs are efficient.  The CSI of Rastra score is 54.36% or in quite proper category and BPNT is 68.94% or proper category.  IPA analysis shows that the most suitable attribute of Rastra is the right on price attribute and for BPNT is the right on amount atrribute.Key words: accurate, BPNT, CSI, efficiency, Rastra